Respuestas

  • Usuario de Brainly
2013-12-04T05:15:13+01:00
2+b=5b-2(3b)

(*) 2(3b) = 6b  ,entonces:

2+b = 5b - 6b

2+b = -b

2 = -b -b

2 = -2b

2/-2 =b

-1 =b


Demostracion:


Si b = -1 , entonces, reemplazamos en la ecuacion:


2+b=5b-2(3b)

2+(-1)=5(-1)-2(3(-1))

2 - 1  =  -5  - 2(-3)

1 = -5  + 6

1 = 1

0 =0

Lqqd. (Lo que queriamos demostrar)


Eso es todo!!1


2013-12-04T05:16:13+01:00
2+b=5b-2(3b)
2+b = 5b-6b
2+b = -b
2b = -2
b = -1

COMPROBACIÓN:

2+b=5b-2(3b)
2+(-1) = 5(-1)-2((3(-1))
2-1 = -5-2(-3)
2-1 = -5+6
1 = 1